Expression, Purification, Refolding, and Characterization of a Neverland Protein From Caenorhabditis elegans - Mao, Shuhong; Song, Zhan; Wu, Mian; Wang, Xiaorui; Lu, Fuping; Qin, Hui-Min (Frontiers in Bioengineering and Biotechnology, 2020)
Steroid hormones that serve as vital compounds are necessary for the development and metabolism of a variety of organisms. The neverland (NVD) family genes encode conserved Rieske-type oxygenases, which are accountable for the dehydrogenation during the synthesis and regulation of steroid hormones. However, the His-tagged NVD protein from Caenorhabditis elegans expresses as inclusion bodies in E. coil BL21(DE3). This bottleneck can be solved through refolding by urea or introduction of maltose-binding protein (MBP) tag at N-terminus. Further research on purification after introduction of maltose-binding protein (MBP) tag at N-terminus, CD measurement and fluorescence-based thermal shift assay indicated that MBP was favorable for the NVD proteins’ solubility and stability, which may be beneficial for large-scale manufacture of NVD protein for further research. The structural model contained Rieske [2Fe-2S] domain and non-heme iron-binding motif, which were similar to 3-ketosteroid 9 α-hydroxylase.